Evaluating the efficiency of entomopathogenic fungi against the Asian longhorned beetle, Anoplophora glabripennis (Coleoptera: Cerambycidae), by using cages in the field - Dubois, T.; Hajek, A.E.; Jiafu, H.; Li, Z. (Oxford University Press, 2004)
Three field experiments using cages were conducted in Anhui, China, to test the efficacy of entomopathogenic fungi against adult Asian longhorned beetles, Anoplophora glabripennis (Motschulsky). The use of two commercially available Beauveria spp. strains, Beauveria bassiana (Balsamo) Vuillemin and Beauveria brongniartii (Saccardo) Petch, applied as cultures in fiber bands fastened around tree trunks, was compared with trunk sprays in the first cage experiment. Longevity of A. glabripennis was decreased by both strains compared with controls, with females killed earlier by B. brongniartii than by B. bassiana. This decrease in longevity was independent of the application method used. In addition, oviposition scars per cage and daily oviposition rate per female were also reduced by both strains, showing a sublethal effect of the entomopathogens. After 10 d, conidial viability was still high on the bands but was drastically reduced when the strains were sprayed onto tree trunks. In the second cage experiment, four strains, proven to be highly pathogenic in the laboratory, were applied as bands alone. During the second cage experiment, daily temperatures were much higher and relative humidities were much lower than during the first cage experiment, and these conditions probably reduced fungal pathogenicity and decreased the sublethal oviposition reduction effect. It was demonstrated that one other B. bassiana strain and one Metarhizium anisopliae (Metchnikoff) Sorokin strain reduced male A. glabripennis longevity. None of the four strains tested had any significant effect on A. glabripennis when applied as 15-d-old bands in a third field experiment.